Challenges and value of peer outreach workers in needle and syringe exchange programs: Evidence from an HIV prevention program in Yunnan province, China. Issue 3 (3rd August 2020) - Haw, Nel Jason; Yang, Jia; Li, Hong; Duo, Lin; Wang, Zetianyu; Bouey, Jennifer Z. H.
Abstract: We aim to compare the values and challenges of peer outreach workers (POWs) with a history of drug use with non-POWs (NPOWs) in a needle and syringe exchange program (NSEP) in Yunnan, China. Data were abstracted from two independent surveys of 98 outreach workers and 33 program managers in 2014. POWs were more likely than NPOWs to conduct active outreach and to report ease in exchanging needles. Commonly cited concerns from POWs were low wages and frustration with client follow-up. Managers expressed the most concern on high turnover rates and low education levels. POWs seem to be more effective than NPOWs in conducting outreach, though POWs face unique challenges. We call for a recognition of the challenges and needs for more sensitive support for POWs.